EFFECT OF PREHEATING TEMPERATURE VARIATION ON MICROSTRUCTURE AND HARDNESS OF WELD OVERLAY CLADDING OF SS400 CARBON STEEL BY SMAW METHOD - paundra, fajar; Rajagukguk, Kardo; Aldyansyah, Dimas; Pujiyulianto, Eko; Muhyi, Abdul (Universitas Negeri Semarang, 2024)
SS400 carbon steel is a type of low carbon steel that has low surface hardness, wears easily, and is not resistant to impact. The application of cladding can reduce the risk of material failure due to the weakness of SS400 carbon steel. In this study, cladding was performed by SMAW method using HV-600 electrodes and a current of 115 A. This welding process causes heat to be concentrated in the melting area, resulting in uneven heating and cooling, so preheating is necessary. This study aims to evaluate the effect of preheating temperature variations of 200°C, 300°C, 400°C, and non-preheating on microstructure and hardness in the cladding process. Macro structural testing shows that the application of preheating can minimize the occurrence of welding defects, and an increase in preheating has an effect on increasing the depth of the HAZ in each specimen tested. Microstructure testing shows that the application of higher preheating will form more ductile phases in the base metal, diffusion layer, HAZ areas. The base metal area has pearlite and ferrite phases. The diffusion layer shows clear boundaries as a result of the diffusion process. The HAZ section forms a fine pearlite microstructure and coarse pearlite and ferrite phases. The weld metal layer is not affected by the preheating temperature used, there are martensite and ferrite phases. Hardness testing on 200oC preheating specimens has the highest hardness in the weld metal of 680.11 HV. Hardness in the diffusion layer, HAZ, and base metal which shows that an increase in preheating temperature affects the decrease in the hardness value of the specimen.